Intracranial hypertension and cortical thickness in syndromic craniosynostosis. (14th February 2020) - Wilson, Alexander T; Den Ottelander, Bianca K; De Goederen, Robbin; Van Veelen, Marie‐Lise C; Dremmen, Marjolein H G; Persing, John A; Vrooman, Henri A; Mathijssen, Irene M J
Abstract : Aim: To evaluate the impact of risk factors for intracranial hypertension (ICH) on cerebral cortex thickness in syndromic craniosynostosis. Method: ICH risk factors including papilloedema, hydrocephalus, obstructive sleep apnea (OSA), cerebellar tonsillar position, occipitofrontal circumference (OFC) curve deflection, age, and sex were collected from the records of patients with syndromic craniosynostosis (Apert, Crouzon, Pfeiffer, Muenke, Saethre‐Chotzen syndromes) and imaging. Magnetic resonance images were analysed and exported for statistical analysis. A linear mixed model was developed to determine correlations with cerebral cortex thickness changes. Results: In total, 171 scans from 107 patients (83 males, 88 females [including repeated scans], mean age 8y 10mo, range 1y 1mo – 34y, SD 5y 9mo) were evaluated. Mean cortical thickness in this cohort was 2.78mm (SD 0.17). Previous findings of papilloedema ( p =0.036) and of hydrocephalus ( p =0.007) were independently associated with cortical thinning. Cortical thickness did not vary significantly by sex ( p =0.534), syndrome ( p =0.896), OSA ( p =0.464), OFC ( p =0.375), or tonsillar position ( p =0.682). Interpretation: Detection of papilloedema or hydrocephalus in syndromic craniosynostosis is associated with significant changes in cortical thickness, supporting the need for preventative rather than reactive treatment strategies. What this paper adds: Papilloedema is associated with thinning of the cerebral cortex in syndromic craniosynostosis, independently of hydrocephalus. What this paper adds: Papilloedema is associated with thinning of the cerebral cortex in syndromic craniosynostosis, independently of hydrocephalus. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. This article is commented on by Hayward on page 771 of this issue. Resumen: Hipertensión intracraneal y grosor cortical en craneosinostosis sindrómica Objetivo: Evaluar el impacto de los factores de riesgo de hipertensión intracraneal (HIC) en el grosor de la corteza cerebral en la craneosinostosis sindrómica. Método: La neuroimagen, y, los factores de riesgo para HIC que incluyeron papiledema, hidrocefalia, apnea obstructiva del sueño (SAOS), posición de la tonsila cerebelosa, edad de desviación de la curva de circunferencia occipitofrontal (CFO) y el sexo, se recogieron de los registros de pacientes con craneosinostosis sindrómica (Apert, Crouzon, Pfeiffer, Muenke, Saethre‐Chotzensis). Las imágenes de resonancia magnética fueron analizadas y exportadas para análisis estadístico. Se desarrolló un modelo mixto lineal para determinar las correlaciones con los cambios en el espesor de la corteza cerebral. Resultados: En total se evaluaron 171 exploraciones de 107 pacientes (83 varones, 88 mujeres [incluyendo escaneos repetidos], edad media 8 años 10 meses, rango 1 año 1 mes – 34 años, DE 5 años 9 meses). El espesor medio cortical en esta cohorte fue de 2, 78 mm (DS 0, 17). Los hallazgos anteriores de papiledema (p=0, 036) y de hidrocefalia (p=0, 007) se asociaron de forma independiente con el adelgazamiento cortical. El grosor cortical no varió significativamente por sexo (p=0, 534), síndrome (p=0, 896), SAOS (p=0, 464), CFO (p=0, 375), o posición tonsilar (p=0, 682). Interpretación: La detección de papiledema o hidrocefalia en la craneosinostosis sindrómica, se asocia con cambios significativos en el grosor cortical. Esto apoya la necesidad de estrategias de tratamiento preventivo en lugar de tratamientos reactivos. Resumo: Hipertensão intracrianiana e espessura cortical na craniossinostose sindrômica Objetivo: Avaliar o impacto de fatores de risco para hipertensão intracraniana (HIC) na espessura cortical em craniossinostose sindrômica. Método: Fatores de risco para HIC incluindo papiloedema, hidrocefalia, apnéia obstrutiva do sono (AOS), posição das tonsilas do cerebelo, idade de deflexão da curva da circunferência occipitofrontal (COF), e sexo foram coletados dos registros de pacientes com craniossinostose sindrômica (síndromes de Apert, Crouzon, Pfeiffer, Muenke, Saethre‐Chotzen) e imagens. As imagens de ressonância magnética foram analisadas e exportadas para análise estatística. Um modelo linear misto foi desenvolvido para determinar correlações com mudanças na espessura do córtex cerebral. Resultados: No total, 171 imagens de 107 pacientes (83 do sexo masculino, 88 do sexo feminino [incluindo varreduras repetidas], média de idade 8a 10m, variação 1a 1m – 34a, DP 5a 9m) foram avaliados. A espessura cortical média nesta coorte foi 2, 78mm (DP 0, 17). Achados prévios de papiloedema ( p =0, 036) e de hidrocefalia ( p =0, 007) foram independentemente associados com a redução cortical. A espessura cortical não variou significativamente com o sexo ( p =0, 534), síndrome ( p =0, 896), AOS ( p =0, 464), COF ( p =0, 375), ou posição tonsilar ( p =0, 682). Interpretação: A detecção do papiloedema ou hidrocefalia na craniossinostose sindrômica se associa com mudanças significativas na espessura cortical, sustentando a necessidade de estratégias de tratamento preventivas e não reativas.